Uji Teratogenitas Ekstrak Bungo Timah (Peperomia pellucida L. Kunth.,) Terhadap Organ Viseral Embrio Mencit Putih (Mus musculus L.) - Sari, Yelvita; Munir, Warnety; Allen, Yohannes (Jurusan Biologi UIN Alauddin Makassar, 2014)
The study on terratogenict effect of Bungo Timah (Peperomia pellucida L. Kunth.,) extract to visceral organ of mice embryo (Mus musculus L) was conducted to identify the effect of P. pelucida extract to development of mice embryo visceral organ. The Complete Randomize Method, which consist of four, extract dose variation: 0; 75; 100; 125 mg/kg BW given from the day 6th-4th of pregnancy were used. The result showed the extract of P. pellucida was not teratogenic at 75 mg/kg BW. While at dose 100 and 125 mg/kg BW showed visceral organ malformation, the cardiac enlargement, right kidney fission, intestinal diverticula, even thought statistically was not significant (P<0,05).Keywords: Mus musculus, organ viseral, Peperomia pellucida (L.) Kunth, teratogenitas